Salmonella Typhimurium Lacking YjeK as a Candidate Live Attenuated Vaccine Against Invasive Salmonella Infection - Park, Soyeon; Jung, Bogyo; Kim, Eunsuk; Hong, Seong-Tshool; Yoon, Hyunjin; Hahn, Tae-Wook (Frontiers in Immunology, 2020)
Non-typhoidal Salmonella (NTS) causes gastrointestinal infection, which is commonly self-limiting in healthy humans but may lead to invasive infection at extraintestinal sites, leading to bacteremia and focal systemic infections in the immunocompromised. However, a prophylactic vaccine against invasive NTS has not yet been developed. In this work, we explored the potential of a ΔyjeK mutant strain as a live attenuated vaccine against invasive NTS infection. YjeK in combination with YjeA is required for the post-translational modification of elongation factor P (EF-P), which is critical for bacterial protein synthesis. Therefore, malfunction of YjeK and YjeA-mediated EF-P activation might extensively influence protein expression during Salmonella infection. Salmonella lacking YjeK showed substantial alterations in bacterial motility, antibiotics resistance, and virulence. Interestingly, deletion of the yjeK gene increased the expression levels of Salmonella pathogenicity island (SPI)-1 genes but decreased the transcription levels of SPI-2 genes, thereby influencing bacterial invasion and survival abilities in contact with host cells. In a mouse model, the ΔyjeK mutant strain alleviated the levels of splenomegaly and bacterial burdens in the spleen and liver in comparison with the wild-type strain. However, mice immunized with the ΔyjeK mutant displayed increased Th1- and Th2-mediated immune responses at 28 days post-infection, promoting cytokines and antibodies production. Notably, the Th2-associated antibody response was highly induced by administration of the ΔyjeK mutant strain. Consequently, vaccination with the ΔyjeK mutant strain protected 100% of the mice against challenge with lethal invasive Salmonella and significantly relieved bacterial burdens in the organs. Collectively, these results suggest that the ΔyjeK mutant strain can be exploited as a promising live attenuated NTS vaccine.